Acetylcholine esterase as a possible marker for the detection of halal way of slaughtering - Rahman, Mohammad Tariqur; Zaman, Rahela; Syed Osman Idid, Syed Zahir Idid; Mohd. Salleh, Hamzah (2010)
Introduction: Different methods of slaughtering are being practiced because of differences in religious guidelines and environmental issues (use of electricity) or convenience of handling etc. Variation in methods of slaughtering results in different conditions namely, release of varying amount of blood and different degree of movement of its body parts prior to death. These issues are related to the release of neurotransmitter (NT) at the neuro-muscular junction (NMJ) eventually is subject to be released from the body through the blood flow. Experimental design: Muscle samples from chicken in small pieces were collected immediately after slaughtering. Slaughtering was carried out using sharp knife. Two different conditions pertaining to the Islamic guidelines of slaughtering were investigated. such as whether the neck was severed (S+) or not (S-) from the body during slaughtering and whether the animal just after slaughtering was released (R+) or not (R-). The level of acetylecholine esterase mRNA involved in the degradation of acetylecholine, a NT at NMJ was investigated by RT-PCR. Results: The level of acetylecholine esterase mRNA was not detected in the sample obtained from the chicken slaughtered following Islamic guidelines i.e., neck should not be severed and body should be released just after the slaughtering (R+S-). Conclusions: Level of acetylcholine or acetylcholine esterase can be used as a biomarker to identify if the slaughtering is performed following Islamic guidelines.